Edukasi Antibiotik dan Swamedikasi, Mencipta Peran Pramuka SMK Kasatrian Solo sebagai Pelopor Pengguna Obat Bijak - Regita Aulia Herabare; Mirzam Arqy Ahmadi; Muhammad Ashar Anas; Farkhan Indy Pangestu (LPPMK Universitas Ngurah Rai, 2025)
Antibiotics are drugs used to treat bacterial infections, but improper use can lead to the emergence of antibiotic resistance. This community service program was conducted at SMK Kasatrian Solo, located in Mendungan, Pabelan, Sukoharjo, where access to health education, especially regarding the correct use of antibiotics and self-medication practices, is still limited. The objectives of this program were to improve the knowledge of Pramuka (Scout) members about appropriate antibiotic use, reduce the risk of misuse, and develop youth cadres who are aware of antibiotic resistance and capable of educating their peers and communities. The educational intervention was delivered through participatory face-to-face sessions. The results showed that the Antibiotic and Self-Medication Education significantly increased participants' understanding of responsible antibiotic use and contributed to building awareness of rational drug behavior among students.